A KINESIOLOGICAL AND PSYCHOLOGICAL STUDY OF THE RATIONAL MOVEMENTS OF ATHLETES IN TRAP SHOOTING DURING THE PREPARATION FOR COMPETITION ROUTINE - Stashkevich, Svetlana; Abramova, Tamara (Revista Inclusiones, 2020)
The paper describes and substantiates the main approaches to studying the dynamics of the functional and emotional state of competitive shooters. In the generally accepted practice of sports physiology and kinesiology, the definition of an athlete's functional state refers to the state of individual body systems (respiratory, cardiovascular, nervous, musculoskeletal systems, psychophysiological indicators, etc.), through which one judges the functional capabilities of the body. The purpose of this paper is to study the influence of objective and subjective factors on the formation of the functional characteristics of the musculoskeletal system and the quality of the exercises in trap shooting. This allows the authors to identify the weak spots in the condition of individual parts of the musculoskeletal system (namely, the upper limbs) and introduce additional exercises/adjustments to the training process that eliminate these imbalances. The use of the kinesiological method makes it possible to objectively assess the functional state of individual parts of the musculoskeletal system (the upper limbs) of athletes and correct it. The study of the emotional state of athletes is expressed in a change in indicators of reactive anxiety, mood, and well-being, indicating the optimization of the functional state of athletes. The results support the continued use of kinesiological and psychological techniques and the continuation of further research.